Vascularized Composite Allotransplantation—An Emerging Concept for Burn Reconstruction. Issue 6 (November 2017) - Ng, Zhi Yang; Lellouch, Alexandre G.; Drijkoningen, Tessa; Chang, Irene A.; Sachs, David H.; Cetrulo, Curtis L.
Abstract : Vascularized composite allotransplantation (VCA) has demonstrated utility in the reconstruction of extensive soft-tissue defects following severe burns. However, pre-VCA events such as multiple transfusions, previous transplantation and pregnancies, the use of skin allografts, and mechanical support devices may result in sensitization and ultimately exclude a burn patient, who may benefit most through VCA, from a hand or face transplant. The authors sought to identify the immunologic challenges involved. All reported VCA cases up to July 2016 were reviewed. Relevant data analyzed include patient demographics, burn etiology, type and extent of VCA performed, pretransplant panel reactive antibody (PRA) status, extent of human leukocyte antigen (HLA) mismatch between donor and recipient, and immunologic outcomes. Of the 142 known cases of VCA to date, 30 (mean age = 36 years) were performed for burn reconstruction (mean interval to surgery = 8.3 years). Thermal and electrical burns were most common and performed in 20 and 30% of all reported upper extremity and craniofacial VCA cases, respectively, despite highly variable pretransplant PRA (0–98%). HLA-matching statuses between donors and recipients varied from 2/6 to 6/6. No obvious relationship could be observed between the incidence and severity of acute rejection with the patient's PRA and HLA-matching statuses, although more extensive treatment was required to reverse rejection episodes in sensitized patients (PRA > 0%). Further development and refinement of clinically relevant immunomodulatory protocols is required to achieve immunosuppression minimization and/or successful transplantation tolerance to enable long-term survival of both the VCA itself and the patient.